Cloning of a gene expressed during appressorium formation by Colletotrichum gloeosporioides and a marked decrease in virulence by disruption of this gene. - Hwang, C S (1995)
Appressorium formation in germinating Colletotrichum gloeosporioides is induced by the surface wax of its host. One of the genes expressed uniquely in C. gloeosporioides during appressorium formation induced by the host signal has been designated cap20, and this gene and its cDNA were cloned and sequenced. Nucleotide sequences of both revealed an open reading frame that could encode a 183-amino acid polypeptide that did not have significant homology with any known proteins. Reverse transcriptase-polymerase chain reaction detected cap20 gene transcripts at the infection front on the surface and within tomato fruits infected by C. gloeosporioides. Gene-disrupted mutants incapable of expressing cap20 showed a drastically decreased virulence on avocado and tomato fruits. These results suggest that cap20 plays a significant role in the infection of the host.